Mitigating channel usage in cooperative caching for Mobile Ad hoc Networks. (14th March 2011) - Gunasekaran, R.; Divya, V.P.; Uthariaraj, V. Rhymend
Cooperative caching supports efficient data dissemination and sharing in Mobile Ad hoc Networks (MANETs). Existing cache consistency maintenance algorithms are stateless, where the data source node is unaware of the cache node status. The stateless algorithm is cost-effective as it does not maintain status and suffers from paying to broadcasting. Stateful algorithms can significantly reduce the consistency maintenance cost by maintaining status of the cached data and selectively propagating the data updates. In this paper, a stateful cache consistency maintenance algorithm, Selective Push and Pull (SPP) is proposed which improves the performance of the MANET by saving the bandwidth and reducing the query delay. Omega Consistency Model is designed to satisfy the user specified consistency.